Fiscal Policy Instruments Based on Indonesian Sharia Principles Linked to Fiscal in the Health Sector - Prasetio, Andri; Janwari, Yadi; Al-Hakim, Sofian (Yayasan Mentari Madani, 2026)
In developing countries, such as Indonesia in general, given the relatively large informal sector, various aspects of subsidized healthcare services provided by the government, both central and regional, are important tools and means for promoting health.Health is one of the many determinants of well-being. Many developing countries worldwide strive to improve the health of their citizens in order to advance the nation's well-being. Indonesia is one of the developing countries implementing public health improvement programs. The health subsidy program is one example of the Indonesian government's focus on supporting national health, and this program has been implemented down to the lowest levels in Indonesia. Some countries have opted for direct provision of health goods, while others combine public service provision with subsidized health insurance for families with incomes below a certain threshold. Both models require identifying families unable to afford health services and the types of services considered public goods. This study aims to explore the development of these programs in relation to the fiscal policies implemented in Indonesia, which have been deemed successful in reducing healthcare costs for poor families. The results indicate a strong correlation between fiscal policy and the provision of healthcare facilities for poor families.